EPIDEMIOLOGY OF DIARRHEA (DIARRHEAL DISEASE): LITERATURE REVIEW - Rahmatia, Rahmatia; Tosepu, Ramadhan (Preventif Journal, 2024)
ABSTRACT Diarrhea is defecation with a soft or liquid consistency, it can even be just water, more often than usual in one day. Diarrhea In general, diarrhea occurs as a result of consuming food and drinks contaminated with viruses, bacteria or parasites. According to the results of a survey conducted by the Ministry of Health, it is known that diarrhea is at the top of the list of 10 diseases that cause hospitalization in Indonesian hospitals.. The aim of this paper is to provide an overview of the epidemiology of diarrheal fever in Indonesia.. The method used in this research is a literature review by searching for relevant articles from electronic databases (Google Scholar). The data analysis technique used is descriptive analysis technique. The research results show several factors that can cause diarrhea in Indonesia, such as age, level of knowledge, nutritional status, hand washing habits. Diarrhea tends to be higher in groups with low education and those who work as farmers/fishermen and laborers. Based on the pattern of causes of death for all ages, diarrhea is the 13th leading cause of death with a proportion of 3.5%. Meanwhile, based on infectious diseases, diarrhea is the 3rd leading cause of death after TB and pneumonia. Based on the results of this research, it is recommended that there be increased implementation of health education by Community Health Centers, especially regarding diarrhea and the importance of clean living behavior and properly boiling drinking water as an effort to prevent diarrhea. Keywords: Epidemiology, Diarrhea